(untitled) (Journal of Fatima Jinnah Medical University, 2025)
ABSTRACT Background: The purpose of this study is to look into the necessity of integrating Interprofessional Education (IPE) into Pakistani undergraduate health professions colleges. The main goal is to evaluate staff and student awareness, attitudes, and perceived barriers regarding IPE. Methods: A mixed-methods approach, combining surveys (n=128) and focused group discussion (n=17), was utilized to obtain comprehensive insights into the perspectives of both students and faculty members over a period of 10 months from medical, dental and nursing colleges. Surveys were distributed to a stratified sample of students and faculty members, evaluating their awareness, perceptions, and challenges related to IPE. Additionally, semi-structured FGD was conducted with a subset of participants to delve deeper into their viewpoints. Descriptive statistics and thematic analysis were employed to analyze the quantitative and qualitative data, respectively. Results: The survey responses and FGD narratives revealed scanty awareness regarding IPE concepts among both students and faculty members. While participants expressed positive attitudes toward IPE, significant challenges such as curriculum constraints, limited resources, and organizational resistance were identified as barriers to effective implementation. The qualitative analysis highlighted the potential benefits of IPE, including improved teamwork, communication skills, and patient-centered care. Conclusion: Despite the acknowledged benefits of IPE, challenges persist that hinder its successful integration. This study advocates for a comprehensive strategy to overcome challenges and promote the effective implementation of IPE, ultimately contributing to more proficient and patient-centric healthcare delivery in Pakistan.